Comparing policy options for carbon efficiency in the wood value chain: Evidence from Austria. (10th April 2021) - Ludvig, Alice; Braun, Martin; Hesser, Franziska; Ranacher, Lea; Fritz, David; Gschwantner, Thomas; Jandl, Robert; Kindermann, Georg; Ledermann, Thomas; Pölz, Werner; Schadauer, Klemens; Schmid, Blasius F.; et al.
Abstract: The current state of research shows that there is big potential for the use of wood, particularly harvested wood products (HWP) to mitigate climate change and increase carbon stocks. Despite of discussions on different accounting approaches, the forest-based sector can contribute with the production of long-lasting wood products to reach international climate goals. This leads to high demands on forests and on what they can deliver both at EU and the national levels. In Austria it has been bemoaned by the Environmental Agency in its recent –eleventh- control report, that a comprehensive concept for the use of wood is missing. The report asks for consideration of increasing future needs for raw wood and energy under considerations of sustainability and under inclusion of all actors involved. Apparently there are some disparities within the different policy instruments. In order to successfully concertise the national policy framework it is of paramount importance to gather the policy actors involved and examine their suggestions for solving the issue. The article is enquiring amongst a number of high level Austrian experts and stakeholders about their perspectives and solutions for enhancing the contribution of the forest based sector to combat climate change. We examine the nature of the suggested instruments and outline the perceived options for action within the capacities of the forest based sector. This is done by way of a triangulation of face-to-face qualitative interviews, moderated focus group discussions and one survey. For the increase in carbon efficiency, all the participants notably emphasise long lasting material use and increase in use. Yet the opinions are contradicting when it comes to energetic use. Our findings indicate that the expert views reflect diverging perspectives on the use of wood for energy consumption. Some opt for policies that support energy consumption of wooden biomass to replace fossil fuels, others want any energy use of wood to become restricted drastically. As a final result, the article derives 16 principle policy measures and instruments that were brought up and assessed by the stakeholders in several rounds of interaction. We conclude that small improvements to existing measures could have ample impacts. Highlights: Material use of long-lasting wood products is first priority policy option. Forest based industry needs to adapt to changes in tree species due to climate change. Material use versus energetic use is the most debated issue by stakeholders. The term "cascadic use" is interpreted differently by stakeholders.